(untitled) (Hekima Review, 2010)
An analysis of the current environmental situation has established that more responsibility is demanded of individuals and societies in order to curb the rapid rate of environmental degradation. Historically, African communities had a deep spiritual link to the environment which was central to a holistic way of life. Formal participatory community-based models of managing the environment found a home within these societies with varying levels of success. The implementation process has not been devoid of conflict due to divergent perspectives and presence of various actors with different interests. Today, pressing realities of poverty and the need to eke a living challenge environmental conservation efforts.